Nationalism and Gender: The 1970s, The Six Million Dollar Man, and The Bionic Woman. - JENKINS, TRICIA (Journal of Popular Culture (John Wiley & Sons, Inc.), 2011)
The article examines the relationship of the U.S. science-fiction television programs "The Six Million Dollar Man" and "The Bionic Woman" to notions of nationalism and understandings of feminism and gender in the 1970s. The negative effects of the U.S. withdrawal from the Vietnam War, the Watergate Scandal, and a scaling back of the U.S. space program on nationalism, and the shows' attempts to assert U.S. technological superiority, are analyzed. In this regard, the author broadly describes developments in the Cold War.